Ice calibration studies for IceCube Upgrade with multi-PMT optical modules, and studies of the sensitivity of future IceCube extensions to astrophysical neutrinos in the MeV and GeV range - Lozano Mariscal, Cristian Jesús (Zenodo, 2023)
The IceCube neutrino observatory is a large-scale particle physics experiment at the South Pole. IceCube consists of a series of sensors embedded in the ice that detect the Cherenkov radiation produced when a neutrino interacts with the ice. Given its great success and reliability, the IceCube detector is being expanded through two extension projects: IceCube Upgrade and IceCube-Gen2. The IceCube Upgrade project aims to install ∼700 new optical modules in a dense configuration in the existing IceCube volume to detect low-energy neutrinos; construction is planned for the Australian summer of 2025-2026. IceCube-Gen2 envisions an expansion of the instrumented volume from 1 to 8 km 3 with new optical modules. Construction is scheduled to begin shortly after the completion of IceCube Upgrade. This expansion will allow IceCube to significantly increase its detection rate of cosmic high-energy neutrinos and further improve our understandingof the universe. This thesis presents the results of simulation studies that evaluate the potential of future detector extensions for a number of topics. The first study focuses on the detection of low-energy neutrinos released during a core collapse supernova (CCSN) with the new IceCube-Gen2 detector when equipped with multi-PMT digital optical modules (mDOMs). It is shown that CCSNe can be detected up to distances of ∼250 kpc with a false detection rate of less than one per century. The second study examines the calibration of bubble column parameters in IceCube Upgrade. The bubble column, a region of frozen ice in the middle of the strings with poorer optical properties than the bulk ice, is a significant source of systematic uncertainties in the current detector, and determining its properties will benefit not only the future detector but also allow improved re-analyzes of existing data. This study shows that its properties can be reconstructed with high precision by lining up two adjacent mDOMs and flashing the LEDs in one of them. The last study investigates the sensitivity of ...